Otolaryngological findings in mucopolysaccharidosis - Yurttaş, Veysel; Bozdemir, Kazım; Tarlak, Behçet; Yazgan, Aylin (ENT Updates, 2014)
A 49-year-old woman admitted to our clinic due to a progressive hoarse voice for 4 years, foreign body sensation in the back of her throat, otalgia, hoarseness and mouth breathing. Nasolaryngoscopy demonstrated a right nasopharyngeal mass extending to oropharynx. Indirect laryngoscopy revealed a granulomatous lesion originating from right band ventricle and extending on the right vocal fold. The granulomatous lesion did not alter correct laryngeal mobility. There was no history of difficulty in swallowing. A contrast enhanced computed tomography showed a smooth mass involving nasopharynx and glottis. A direct laryngoscopy was planned for excisional biopsy of the lesion. Histopathological examination revealed nasopharyngeal and laryngeal amyloidosis. Further evaluations were negative for systemic amyloidosis. The aim of the report is to present an extremely rare case of isolated primary nasopharyngeal and laryngeal amyloidosis and discuss by using current literature knowledge.